Inotropic effect of low extracellular sodium on perfused perinatal rat heart - Ost'ádalová, I; Kolár, F; Ost'ádal, B (Canadian journal of physiology and pharmacology, 1995)
The purpose of the present study was to estimate the development of the inotropic response to low extracellular sodium (LES) during the perinatal period. The effect of LES (35 mmol.L-1) was measured in isolated perfused control and ryanodine-pretreated rat hearts on prenatal day 20 and postnatal days 1, 2, 4, and 7. The effect of LES on the developed force (DF) of control hearts changes significantly day by day: whereas a persisting increase of magnitude of contractions was recorded in the prenatal hearts, this increase was only transient on postnatal day 1 and 2. Starting from day 4, the initial signs of a triphasic response, typical for adult hearts, appeared (an initial increase of DF, followed by a decrease of DF and a rise of resting force, and finally a delayed increase of DF); this trend was more pronounced on day 7. The LES-induced increase of resting force was recorded only in 2-, 4-, and 7-day-old hearts. The negative inotropic effect of ryanodine (10(-6) mol.L-1) was observed already prenatally (60% of the controls) and continued during the whole period of investigation; in contrast, a ryanodine-induced increase of resting force was recorded only postnatally. However, pretreatment with ryanodine abolished the day-by-day changes in the response to LES: in all the hearts studied, the first phase (initial increase of DF) was followed by a severe depression of the magnitude of contractions, together with increased resting force. Our data show significant age-dependent differences in the cardiac contractile response to LES.(ABSTRACT TRUNCATED AT 250 WORDS)
Keywords: Calcium; Sarcoplasmic Reticulum; Myocardial Contraction; Sodium; velikost orgánu; techniky in vitro; Pregnancy; vápník; pumpa pro výměnu sodíku a vápníku; novorozená zvířata; Female; Sodium-Calcium Exchanger; krysa rodu Rattus; zvířata; potkani Wistar; transportní proteiny; Carrier Proteins; Animals, Newborn; ženské pohlaví; Rats, Wistar; Male; ryanodin; sodík; těhotenství; Ryanodine; In Vitro Techniques; kontrakce myokardu; Rats; myokard; Body Weight; Animals; Organ Size; sarkoplazmatické retikulum; tělesná hmotnost; mužské pohlaví; Myocardium